2019
DOI: 10.2337/db18-0933
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Methylglyoxal-Induced Progenitor Cell Dysfunction for Tissue Repair in Diabetes

Abstract: Patient-derived progenitor cell (PC) dysfunction is severely impaired in diabetes, but the molecular triggers that contribute to mechanisms of PC dysfunction are not fully understood. Methylglyoxal (MGO) is one of the highly reactive dicarbonyl species formed during hyperglycemia. We hypothesized that the MGO scavenger glyoxalase 1 (GLO1) reverses bone marrow-derived PC (BMPC) dysfunction through augmenting the activity of an important endoplasmic reticulum stress sensor, inositol-requiring enzyme 1α (IRE1α), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…In particular, the ability of RSV to protect endothelial cells, not just because of its unspecific direct antioxidant properties, but through the activation of the SIRT1-GLO1 pathway, may be of great relevance. In fact, many experimental and clinical studies confirmed that GLO1 inducers and/or dicarbonyl scavengers represent potential effective agents to reverse or limit diabetes-related complications [70,91,92,93,94].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the ability of RSV to protect endothelial cells, not just because of its unspecific direct antioxidant properties, but through the activation of the SIRT1-GLO1 pathway, may be of great relevance. In fact, many experimental and clinical studies confirmed that GLO1 inducers and/or dicarbonyl scavengers represent potential effective agents to reverse or limit diabetes-related complications [70,91,92,93,94].…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion deriving from the existent studies is that the dysregulation of VEGF action by dicarbonyl stress sustains aberrant angiogenesis. In line with this, the overexpression of Glo1 inhibits AGEs formation in ECs [133], favors both angiogenesis in vitro [134] and in vivo facilitating wound healing [135] and muscle reperfusion after ischemic insults in diabetic rats [136]. Our group has recently identified the antiangiogenic factor Homeobox A5 (HoxA5) as a new player in MGO-induced angiogenesis impairment of ECs knock-down for Glo1.…”
Section: Dicarbonyl Stress In Aging-related Diseasesmentioning
confidence: 94%
“…PDLFs were relatively resistant to toxicity induced by exogenous MG: incubation of PLDFs with 25-1000 µM for 2 days produced growth arrest and toxicity at ≥200 µM MG-a concentration profoundly greater than physiological extracellular concentrations of MG. The median growth inhibitory concentration GC 50 Pathophysiology/complications flux of glucose consumption by PDLFs ( figure 2G). There was no net increase in formation of L-lactate ( figure 2H).…”
Section: Dicarbonyl Stress In Human Periodontal Ligament Fibroblasts mentioning
confidence: 99%
“…This involved correction of the UPR stress sensor of the ER, inositol requiring enzyme 1α. 50 tRES-HESP was optimized for induction of expression of Glo1 by activation of Nrf2 with median effective concentration EC 50 of 1.46 µM. 19 Other Nrf2-regulated genes are implicated in the prevention of metabolic dysfunction induced by HG concentration in PDLFs in culture: increased expression of G6PD (see above) and γ-glutamylcysteine ligase, catalytic and modifier subunits (γ-glutamylcysteine ligase and γglutamylcysteineligase, modifier subunit)-likely mediating the increase in cellular GSH in both LG and HG concentration cultures.…”
mentioning
confidence: 99%